Inherent optical properties and particulate matter distribution in summer season in waters of Hornsund and Kongsfjordenen, Spitsbergen - Sławomir Sagan; Mirosław Darecki (Oceanologia)
Two Spitsbergen fjords, Hornsund and Kongsfjorden, are known for being under different hydrological regimes. The first is cold, separated from warm Atlantic water by East Spitsbergen Current, while Kongsfjorden is frequently penetrated by relatively warm Atlantic water. On the other hand, both are under strong influence of water discharge from glaciers and land freshwater input. During the period of observation in both fjords a dominant water mass was Surface Water, which originates mainly from glacial melt. The presence of suspended matter introduced with melt water in Surface Water is reflected by highest values of light attenuation and absorption coefficients recorded in areas close to glacier both in Hornsund and Kongsfjorden. In Hornsund the maximum light attenuation coefficient cpg(555) was 5.817 m−1 and coefficient of light absorption by particles ap(676) = 0.10 m−1. In Kongsfjorden the corresponding values were 26.5 m−1 and 0.223 m−1. In Kongsfjorden suspended matter of the size class 20–200 μm dominated over fractions smaller than 20 μm while in Hornsund dominating size fraction was 2–20 μm. The results provide an evidence of considerable range of variability of the optical properties mainly due to glacial and riverine runoff. The scale of variability of particulate matter in Kongsfjorden is bigger than in Hornsund. Most of the variability in Hornsund can be attributed to glaciers discharge and a presence of particles of mineral origin, while in Kongsfjorden the organic and mineral particles contribute almost equally to defining the optical properties of water.